2005
DOI: 10.1111/j.1460-9568.2005.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Newly born cells in the ageing dentate gyrus display normal migration, survival and neuronal fate choice but endure retarded early maturation

Abstract: Addition of new granule cells to the dentate gyrus (DG) from stem or progenitor cells declines considerably during ageing. However, potential age-related alterations in migration, enduring survival and neuronal fate choice of newly born cells, and rate of maturation and dendritic growth of newly differentiated neurons are mostly unknown. We addressed these issues by analysing cells that are positive for 5'-bromodeoxyuridine (BrdU), doublecortin (DCX), BrdU and DCX, and BrdU and neuron-specific nuclear antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
211
7
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(241 citation statements)
references
References 73 publications
(116 reference statements)
22
211
7
1
Order By: Relevance
“…This finding is surprising in the light of earlier observations in rat models that a dramatic decline in the proliferation of NSCs occurs in the DG between young and old age (Olariu et al 2007;Rao et al 2006), but NSC numbers are preserved in the SGZ during the course of aging (Hattiangady and Shetty 2008). Furthermore, most studies on rodent models point out that proliferation of far fewer NSCs in the aged DG underlies the age-related reduction in net hippocampal neurogenesis (Cameron and McKay 1999;Hattiangady and Shetty 2008;Heine et al 2004;Kuhn et al 1996;McDonald and Wojtowicz 2005;Rao et al 2005;Seki and Arai 1995;Walter et al 2011but see Encinas et al 2011. Consistent with this, other studies have shown that aging in the hippocampus is associated with alterations in NSC proliferation factors such as decreased concentrations of neurotrophic factors that are mitogenic to NSCs Shetty et al 2005;Zeng et al 2011).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This finding is surprising in the light of earlier observations in rat models that a dramatic decline in the proliferation of NSCs occurs in the DG between young and old age (Olariu et al 2007;Rao et al 2006), but NSC numbers are preserved in the SGZ during the course of aging (Hattiangady and Shetty 2008). Furthermore, most studies on rodent models point out that proliferation of far fewer NSCs in the aged DG underlies the age-related reduction in net hippocampal neurogenesis (Cameron and McKay 1999;Hattiangady and Shetty 2008;Heine et al 2004;Kuhn et al 1996;McDonald and Wojtowicz 2005;Rao et al 2005;Seki and Arai 1995;Walter et al 2011but see Encinas et al 2011. Consistent with this, other studies have shown that aging in the hippocampus is associated with alterations in NSC proliferation factors such as decreased concentrations of neurotrophic factors that are mitogenic to NSCs Shetty et al 2005;Zeng et al 2011).…”
Section: Discussionmentioning
confidence: 88%
“…This phenomenon has received widespread attention because of its perceived role in functions such as learning, memory, and mood (Aimone et al 2006;Clelland et al 2009;Drapeau et al 2003;Dupret et al 2007;Eisch et al 2008;Imayoshi et al 2008;Jessberger et al 2009;Kee et al 2007;Kuhn et al 1996;Leuner et al 2006;Sahay and Hen 2007;Santarelli et al 2003). However, the extent of neurogenesis progressively declines with age resulting in~90 % decline in old age (Kuhn et al 1996;Rao et al 2005Rao et al , 2006. As old age is also associated with decreased ability for hippocampaldependent learning and memory function and increased incidence of depression, there is a widespread interest to understand the mechanisms underlying the age-related decrease in neurogenesis and to develop strategies that increase neurogenesis in the aged hippocampus (Bachstetter et al 2008;Bernal and Peterson 2004;Lie et al 2005;Drapeau and Abrous 2008;Hattiangady et al 2007;Jessberger and Gage 2008;Miranda et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The decline is largely attributable to a reduction in proliferation of neuronal precursor cells, although evidence also implicates a decrease in neuronal fate determination (e.g., Kempermann et al, 1998) or slowed maturation of adult-born neurons in senescence (Rao et al, 2005). The age-dependent decline in neurogenesis appears to be mediated by age-related alterations in the cellular microenvironment rather than impaired responsiveness of progenitor cells to neurogenic stimuli.…”
Section: Agementioning
confidence: 99%
“…; Sigma, St. Louis, MO) for 10 consecutive days to label dividing cells. This injection regimen was based on past research designed to capture the impact of a variety of manipulations on cell proliferation and survival in the hippocampus (Kempermann et al, 1997;Lee, et al, 2002a;Rao et al, 2005;Glenn et al, 2007), and to parallel the time point that prenatal choline protects against seizure-induced memory deficits (Yang et al, 2000;Holmes et al, 2002).…”
Section: Induction Of Status Epilepticus and Bromodeoxyuridine Injectmentioning
confidence: 99%